ANALISIS PENERAPAN METODE BERMAIN PERAN DALAM MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA 5–6 TAHUN DI PAUD - Ujung, Asnita; Agustini, Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language ability is an important aspect of early childhood development because it is related to children's ability to communicate, express ideas, understand information, and interact with their environment. Initial observations indicated that some children aged 5–6 years were still reluctant to speak, had limited vocabulary, and had difficulties expressing ideas and responding to conversations. This study aimed to analyze the implementation of role-playing methods in developing the language abilities of children aged 5–6 years in an early childhood education setting. The study employed a descriptive qualitative approach and was conducted at Fajar Harapan Kindergarten, Tolang Village, Sipirok District, South Tapanuli Regency, from April to July 2026. The participants consisted of 25 children in Group B, with the classroom teacher and school principal serving as informants. Data were collected through observation, interviews, and documentation and analyzed through data condensation, data display, and conclusion drawing and verification. Data validity was established through source and technique triangulation. The findings showed that role-playing activities provided opportunities for children to actively use language through conversations and interactions during play. Development was observed in children's speaking abilities, vocabulary use, sentence construction, listening, responding, expressing ideas, and confidence in communicating. The teacher's role as a facilitator through the selection of themes relevant to children's experiences, open-ended questions, guidance, and opportunities to develop dialogue also supported children's language development. Role-playing can therefore serve as an alternative learning method that provides active, contextual, and enjoyable language experiences for children aged 5–6 years.